Are invasive species a phylogenetically clustered subset of naturalized species in regional floras? A case study for flowering plants in China. (16th July 2022) - Qian, Hong; Rejmánek, Marcel; Qian, Shenhua
Abstract: Aim: We test (1) whether invasive angiosperm (flowering plant) species are a phylogenetically clustered subset of all naturalized angiosperm species within an angiosperm assemblage, (2) whether more harmful invasive species are more strongly, or less strongly, related to each other, (3) whether the result of the first test is consistent with those for geographic regions distributed in substantially different climatic conditions, and (4) whether patterns of phylogenetic relatedness for invasive species in regions across climatic gradients are consistent with those for overall naturalized species. Location: China. Time period: Current. Taxon: Angiosperms (flowering plants). Methods: We recognized 28 province‐level regions in China and collated naturalized and invasive species lists of angiosperms for each region. Two phylogenetic metrics (i.e., net relatedness index and nearest taxon index), which represent different depths of evolutionary history, were used to quantify phylogenetic relatedness of angiosperms in China and in each region. Values of the metrics of phylogenetic relatedness were related to temperature and precipitation. Results: At the national scale, invasive assemblage is a phylogenetically clustered subset of the naturalized species pool. More harmful invasive species are more strongly clustered. At the regional scale, both naturalized and invasive species are phylogenetically clustered subsets of the national naturalized species pool. Furthermore, invasive species in regional floras are also phylogenetically clustered subsets of their respective regional naturalized species pools. Main conclusions: Invasive angiosperm species are a phylogenetically clustered subset of naturalized angiosperm species. More harmful invasive species are more strongly clustered with respect to their naturalized species pools, compared to less harmful invasive species. Our findings have significant implications to predicting and controlling invasive species based on phylogenetic relatedness among naturalized species.